Calcitonin gene-related peptide monoclonal antibodies and medication overuse headache: is stopping excessive pain medication still necessary? - João José Freitas de Carvalho (Arquivos de Neuro-Psiquiatria)
Recent studies demonstrate a significant paradigm shift concerning migraine patients suffering from medication overuse (MO). Traditionally, doctors used to demand that patients who overused medications be withdrawn before beginning any preventive therapy; however, such a belief has recently been challenged by emerging evidence about the benefit of calcitonin gene-related peptide monoclonal antibodies (CGRP mAbs), which have shown similar effectiveness in several clinical trials and real-world studies, regardless of whether a patient has previously stopped taking excessive medications. The data indicates that patients undergoing CGRP mAb therapy naturally decreased their acute medication consumption as migraine frequency diminished without requiring forced discontinuation. Furthermore, safety analyses have confirmed favorable tolerability profiles when CGRP mAbs are administered concurrently with various acute medications. This new evidence-based approach offers several clinical advantages, including enhanced treatment adherence and reduced risk of withdrawal complications. These findings support transitioning from mandatory detoxification protocols toward more individualized treatment strategies, representing a significant advancement in clinical migraine management.